Emerging New Roles of GM130, a cis-Golgi Matrix Protein, in Higher Order Cell Functions - Nobuhiro Nakamura (Elsevier, 2010)
GM130 is a peripheral membrane protein strongly attached to the Golgi membrane and is isolated from the detergent and salt resistant Golgi matrix. GM130 is rich in coiled-coil structures and predicted to take a rod-like shape. Together with p115, giantin, and GRASP65, GM130 facilitates vesicle fusion to the Golgi membrane as a vesicle "tethering factor". GM130 is also involved in the maintenance of the Golgi structure and plays a major role in the disassembly and reassembly of the Golgi apparatus during mitosis. Emerging evidence suggests that GM130 is involved in the control of glycosylation, cell cycle progression, and higher order cell functions such as cell polarization and directed cell migration. This creates the potential for novel Golgi-targeted drugs and treatments for various diseases including glycosylation defects, immune diseases, and cancer. Keywords:: vesicular transport, membrane, organelle inheritance, golgin, congenital disorder of glycosylation